2022
DOI: 10.1057/s41599-022-01269-3
|View full text |Cite
|
Sign up to set email alerts
|

The effects of government policies targeting ethics and governance processes on clinical trial activity and expenditure: a systematic review

Abstract: Governments have attempted to increase clinical trial activity in their jurisdictions using a range of methods including simplifying the ethics review and governance process of clinical trials. This study’s objective was to systematically review the effects of government actions targeting ethics reviews or governance processes on clinical trial activity. The data sources of Pub Med, Scopus, Sage, ProQuest, Google, Google Scholar and reference lists were all searched between 9/8/20 and 6/9/20. From these source… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 26 publications
(66 reference statements)
0
1
0
Order By: Relevance
“…The positive association of governance interventions with shorter time to governance approval observed in these analyses supports the implementation of governance processes that define the scope of governance review (resulting in a median difference of 51 days) and triage projects according to risk (resulting in a median difference of 57 days). The alignment of the favourable findings for these interventions in the current analyses with positive findings for these types of interventions in prior reports provides further support for their likely value [9].…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…The positive association of governance interventions with shorter time to governance approval observed in these analyses supports the implementation of governance processes that define the scope of governance review (resulting in a median difference of 51 days) and triage projects according to risk (resulting in a median difference of 57 days). The alignment of the favourable findings for these interventions in the current analyses with positive findings for these types of interventions in prior reports provides further support for their likely value [9].…”
Section: Discussionsupporting
confidence: 78%
“…The observation that schemes that support mutual acceptance of ethics review were associated with shorter overall time to site activation provides additional support for a likely benefit from this strategy. Prior research has also identified mutual acceptance of ethics review as a priority ethics intervention and the totality of the evidence across this study and prior investigations suggests it is likely to be effective [9,17]. Based on the current data, there remains greater uncertainty about the value of scope guidelines and triaging of ethics applications though both are inherently appealing.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Past literature reviews show that jurisdictions seeking to reduce their ethics and governance approval times most commonly implement several such interventions and disentangling the effects of each can be di cult. 13 Some sites have recently reported use of "integrated models" where trial design and ethics review are done concurrently with members of the ethics review panel attending and contributing to project planning meetings. This was in place in at least one state in Australia during the pandemic years.…”
Section: Discussionmentioning
confidence: 99%